To the question of the efficiency young pacific salmon at fish farms of the Sakhalin region - O. V. Zelennikov; M. S. Myakishev (Известия ТИНРО, 2022)
Effectiveness of the salmon juveniles feeding was examined during six cycles of fish breeding for pink salmon Oncorhynhus gorbuscha, chum salmon O. keta, cherry salmon O. masou, and coho salmon O. kisutsh at 12 fish hatcheries belonged to the Sakhalin branch of FBSI Glavrybvod with using of different starter feeds produced by Aller Aqua (Denmark) and Aquatech (Russia). All hatcheries worked in the coldwater regime of rearing. Both feeds were rather effective for all species that was evidenced by low feeding coefficients, usually 0.6–0.8. Anyway, average value of the feeding coefficient was lower for the starter feed Aquatech at all factories. Beyond a high quality of this feed, its availability in two variants of flotation was important, as the slowly sinking and floating forms. The floating food was found to be more suitable for the growing juvenile pink salmon at all farms. On the other hand, both starter feeds were suitable for chum salmon, their priority for this species depended on fish farm and obviously was determined by combination of many factors, such as temperature conditions, configuration of canals and ponds, their hydrodynamics, feed dispensers, etc.